Left ventricular mass formulae and prevalence rates of echocardiographic left ventricular hypertrophy in Nigerians with essential hypertension - Adekunle, Ajayi; Adeseye, Ajayi; Adebayo, Oyedeji; Olatayo, Adeoti; Joseph, Omotoye; Ayodele, Adebayo (North American journal of medical sciences, 2013)
Background: Left ventricular hypertrophy (LVH) as a marker of cardiac damage in hypertension has important prognostic implications. With high prevalence of hypertension in Nigeria and the untoward effect of LVH, it is essential that the prevalence of LVH be determined. Aims: To determine prevalence of LVH and its severity in clinical practice among hypertensive patients referred for echocardiographic assessment in Nigeria. Materials and Methods: Devereux and Troy formulae were used to calculate echocardiographic LV mass (LVM) in 401 subjects and thereafter normalized to body surface area (BSA), heigth 2 (ht 2 ) and height 2.7 (ht 2.7 ) to define LVH to standard gender-specific thresholds. Results: Mean age was 53.22 ± 16.56 years (male = 53.18 ± 15.80; female = 53.27 ± 17.43; P = 0.958) with a male:female ratio of 1.13:1. Prevalence rates of LVH ranged between 38.9-51.3% using the Devereux Formula and 62.4-71.1% using the Troy formula. LVM/(ht 2.7 ) using the Troy formula gave the highest prevalence rate of LVH. Majority of the patients with LVH had severe form of hypertrophy with the prevalence rates ranging from 22.3% (LVM/BSA; Devereux formula) to 47.1% (LVM/ht 2.7 ; Troy formula). Conclusion: Prevalence of LVH by any echocardiographic criteria is high. There is a need to come to a consensus on the best formula and indexing variables, that will unify the reporting of LVH.